PERUM DANAREKSA SEBAGAI HOLDING BUMN TERHADAP PENGELOLAAN ASET NEGARA DALAM PRESPEKTIF HUKUM BISNIS SYARIAH - Ema Nurkhaerani; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
The transformation of BUMN is an important part of national development that is oriented towards the welfare of the people. Perum Danareksa was appointed as the holding company in the financial sector through Government Regulation Number 113 of 2021. This transformation is strengthened by Law Number 1 of 2025 concerning SOEs which adopts the principle  of business judgment rule. The Holding structure is expected to be able to create efficiency, synergy, and increase the competitiveness of state corporations. However, when viewed from the perspective of sharia business law, BUMN governance is not enough to only emphasize profits, but also must fulfill the principles of justice (al-'adl), trust, usefulness (maslahah), and avoid the practice of riba, gharar, and maysir. This research uses a normative juridical approach with a legal and conceptual approach. The results of the study show that Danareksa's holding model is legally positive and benefits the efficiency of state assets. However, part of the portfolio is still placed in conventional interest-bearing instruments, which in sharia it is considered problematic. This poses a challenge so that the management of state assets is in line with Islamic values that emphasize justice and benefits. By strengthening  the Sharia Governance framework, increasing transparency, and expanding sharia instruments such as sukuk and sharia mutual funds, Danareksa has the potential to become a model of BUMN governance that is not only modern, but also ethical and in accordance with Islamic principles.